Hubungan antara Ketergantungan Penggunaan Smartphone dan Minat Interaksi Sosial Asosiatif pada Siswa SMP - Asit, Vanensia Eufamia; Lay, Andriyani Emilia; Apriliana, I Putu Agus; Puspitasari, Weni (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2025)
Globally, smartphone use among adolescents, including junior high school students, has increased significantly. However, excessive use raises concerns about dependency, which may influence social interactions. A common phenomenon is that students tend to focus more on their smartphones even when engaged in group activities, thereby reducing face-to-face interactions such as greeting or joking with peers. This study aimed to examine the relationship between smartphone dependency and associative social interaction interest among junior high school students. A correlational approach was employed with a sample of 69 students selected through proportionate stratified random sampling. Data were collected using a smartphone dependency questionnaire and an associative social interaction interest questionnaire. The findings revealed that 39.1% of students demonstrated a moderate level of smartphone dependency, while 40.6% showed a moderate level of associative social interaction interest. Product-moment correlation analysis indicated a significant positive relationship between smartphone dependency and associative social interaction interest (r = 0.424 > r table = 0.2404; p < 0.05). These results suggest that high smartphone usage does not reduce students’ social interaction interest but rather shifts the interaction pattern from direct to indirect. Adolescents tend to be more engaged in digital social interactions, which allow them to maintain connections with peers and parents. Future research is recommended to employ qualitative methods to gain deeper insights into factors influencing associative social interaction among junior high school students.